Diagnóstico ambiental e uma proposta de uso da bacia hidrográfica do córrego Bebedouro Uberlândia/ MG - Santos, Carla Rodrigues (2008)
This study aimed to achieve an environmental diagnosis and a proposal to use correctly Bebedouro s stream basin in Uberlândia/MG, using geoprocessing techniques. The basin is located in the rural area in the north of Uberlândia s urban zone. Distant 10km from downtown, among the coordinates 780500 787800 mE and 7917200 to 7925000 mN, presenting an area of 32,56km², where it was built a hydroelectric usine Amador Aguiar II , former AHE Capim Branco II. To accomplish this study, we used: climatological data, cartographic documents, aerial photographs from 1979 and images from HRVIR/Spot satellites, from 2006. The methodology adopted was based on a proposal by Libault (1971), which defines four research levels: the compilatory, correlative, and semantic rules. The software uses was the Cartalinx (for conversion of analog products), Idrisi (data processing) and ArcView (final layout production). As a result of the research about Bebedouro s stream basin, is that it has a tropical climate, with annual precipitation index of 1540mm, and an annual temperature average of 22.9º C, and the highest average of maximum temperatures is in October (31.1º C) and the lowest average of minimum temperatures is in July (14.6 º C). The geological formation is Serra Geral which occupies 76.45% of the area, formed by basaltic spills. The soils are red distoferric latosoil occurs in 76.70% of the basin s area. Most of the area is 69% between altitudes from 600 to 780 meters. The use of the land and vegetation, both prevalent as in 1979 as in 2006 are pastures, followed by forests/ cerradão , agriculture and cerrado . In 1979 the pastures occupied 60.42% of the area, while in 2006 it increased slightly to 64.19%. The category forest/ cerradão , also increased during the period observed, from 15.04% to 15.61% (2006). In categories such as agriculture and cerrado decreased. Agriculture increased from 13.04% (1979) to 11.99% (2006), while cerrado changed from 8.46% (1979) to 55.95% (2006). What we conclude is that in the basin the anthropic use predominates and such changes in the use of land are old, or occurred before 1979. Most of the basin, or in 84% of the losses occur in soil, less than 6 ton/ha a year. It is characterized by the presence of small properties, smaller than 30ha (60% of them) and 46% of the owners live on the farm for more than 20 years). From the intersection of maps, a landuse map had been drawn up for Bebedouro s steam basin, where we concluded that in 18.09% of the area can be used for farming and grazing, without the necessity of complex conservationists ways. In 48.74% of the area anthropic activities can be developed, especially the grazing, however it requires conservationists ways, as an example the construction of level curves and most often terraces. In 28.19% of the area shouldn be used with antropic activities, it is intended to recover the original vegetation, and 4.98% should be designed to permanent preservation the recommended Bebedouro s stream basin Uberlãndia/MG landuse map indicates how the area should be occupied, in order to minimize environmental impacts and contribute to the preservation of water resources, for a and fauna of the river. The geoprocessing techniques used for the development of this study have proved themselves very satisfactory and contributed to the products development used in the necessary environmental diagnosis and recommendation for the basin use.